2019
DOI: 10.1002/cam4.2710
|View full text |Cite
|
Sign up to set email alerts
|

High pretreatment plasma Epstein‐Barr virus (EBV) DNA level is a poor prognostic marker in HIV‐associated, EBV‐negative diffuse large B‐cell lymphoma in Malawi

Abstract: Plasma Epstein-Barr virus (EBV) DNA measurement has established prognostic utility in EBV-driven lymphomas, where it serves as a circulating tumor DNA marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
1
13
1
Order By: Relevance
“…1,11,[19][20][21] Montgomery et al confirmed that high plasma pre-EBV DNA was an adverse prognostic marker for DLBCL patients. 22 But circulating tumor cells or other EBV-infected cells should also be considered to reflect the patient's EBV DNA load. Therefore, we analyzed the differential expression of whole blood EBV DNA in lymphomas and its relationship with prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,11,[19][20][21] Montgomery et al confirmed that high plasma pre-EBV DNA was an adverse prognostic marker for DLBCL patients. 22 But circulating tumor cells or other EBV-infected cells should also be considered to reflect the patient's EBV DNA load. Therefore, we analyzed the differential expression of whole blood EBV DNA in lymphomas and its relationship with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…EBV DNA load is highly correlated with the prognosis of types of lymphoma. [22][23][24][25] Previous study has shown that among NKTL patients who received L-asparaginase-based SMILE regimen, those with a higher EBV DNA load also had a poorer prognosis. 26 Our study had shown that there were disparities in whole blood EBV DNA loads among different lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer studies have been performed measuring EBV in peripheral blood of PLWH to determine its value as a diagnostic tool and prognostic factor. In this regard, the detection of EBV load has been reported to be more frequent among lymphomas in PLWH than in the general population [ 25 , 208 , 209 ]. Moreover, some studies, including ours, have suggested that EBV load measured in plasma could be a useful tool for the diagnosis of NHL and HL in PLWH, since EBV has been detected in plasma of these patients at lymphoma diagnosis [ 210 , 211 ].…”
Section: Implications Of Ebv Load In Hiv-related Lymphomamentioning
confidence: 99%
“…Some studies have pointed out that the presence of EBV in peripheral blood could be used as a prognostic factor in HRL. Individuals with high levels of EBV load in plasma have shown worse OS [ 25 , 209 , 210 , 211 ]. In this regard, Muncunill et al reported a negative impact of high EBV load on the survival of HIV-related NHL treated without rituximab.…”
Section: Implications Of Ebv Load In Hiv-related Lymphomamentioning
confidence: 99%
“…The impact of HIV infection on the disease incidence of EBV-associated LPDs is less clear. High plasma EBV DNA level was identified as a poor prognostic factor associated with reduced OS in HIV-associated, EBV-negative DLBCL in Malawi ( 188 ). However, diagnosis of EBV-association via in-situ-hybridization for EBER is not a common practice in most countries in the Africa continent and there is a limitation on the cancer registry data.…”
Section: Hiv and Ebv+ Lymphomas In Sub-saharan Africamentioning
confidence: 99%